2023
DOI: 10.1039/d3ja00025g
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of gas cell reactions for 70+ elements using N2O for ICP tandem mass spectrometry measurements

Abstract: Gas cell interactions of 73 elements with nitrous oxide (N2O) have been evaluated using inductively coupled plasma tandem mass spectrometry (ICP-MS/MS). Recommendations for the reduction of interferences are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…It is notable that the results for the mass-shift measurements obtained with ozone as the cell gas in the present work roughly showed similar trends of the reactions in the periodic table to those observed with N 2 O as the cell gas reported by Lancaster et al 8 It can be expected that on-line generated ozone can be an alternative of N 2 O as the cell gas, free from the management of a poisonous gas. In addition, because ozone is a pure substance of oxygen, while N 2 O is a compound of nitrogen and oxygen, it can be expected that the reaction between an ion and ozone will be better controlled with much less multi-atomic clusters, resulting in relatively higher sensitivity for the measurement.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…It is notable that the results for the mass-shift measurements obtained with ozone as the cell gas in the present work roughly showed similar trends of the reactions in the periodic table to those observed with N 2 O as the cell gas reported by Lancaster et al 8 It can be expected that on-line generated ozone can be an alternative of N 2 O as the cell gas, free from the management of a poisonous gas. In addition, because ozone is a pure substance of oxygen, while N 2 O is a compound of nitrogen and oxygen, it can be expected that the reaction between an ion and ozone will be better controlled with much less multi-atomic clusters, resulting in relatively higher sensitivity for the measurement.…”
supporting
confidence: 90%
“…As a more reactive cell gas for ICP-QMS/QMS, nitrous oxide was investigated for the measurement of various elements, such as rare earth elements, Cl, P, Ra, S, Si, and Sr. 8–13 There are also reports of using other gases to improve reactions in the reaction cell of ICP-QMS/QMS; for example, carbonyl sulfide and carbon dioxide, respectively. 14,15 These works showed that selecting a more reactive cell gas helps in improving spectral interferences.…”
mentioning
confidence: 99%
“…The suitability and accuracy of the method were checked by analyzing the geological CRM, QLO-1 (USGS), and also by comparing the data with the results obtained by INAA (Table 6). Lancaster et al [114] made investigations on the use of N2O as a reaction gas for the determination of 73 elements including REEs. However, the authors did not conduct any application studies on geological materials.…”
Section: Icp-tandem Mass Spectrometry (Icp-ms/ms)mentioning
confidence: 99%
“…Wie jüngste Arbeiten an der Montanuniversität Leoben gezeigt haben, hat Lachgas als Reaktionsgas noch bessere Eigenschaften und senkt aufgrund seiner besonders starken Reaktivität für einige TCEs die Nachweisgrenzen um den Faktor zehn. 14,15) Blätter als Filter…”
Section: Auf Einen Blickunclassified